Giant kidney worm: novel report of Dioctophyma renale in the kidney of a dog in Greece - Angelou A.; Tsakou K.; Mpranditsas K.; Sioutas G.; Moores D. Anderson; Papadopoulos E. (Helminthologia, 2020)
Dioctophyma renale is the largest nematode that infects domestic mammals and is the aetiologic agent of a serious renal disease, dioctophymatosis. It has an indirect life cycle with carnivores serving as final hosts and earthworms as intermediate hosts. The parasite can infect humans with signifi cant zoonotic potential. The pathogenesis of dioctophymatosis is mainly associated with the extent of renal atrophy caused by the parasites, the risk of bilateral renal infestation and the location of the parasite (extrarenal cases). Clinical diagnosis is challenging, and the only treatment option is nephrectomy or nephrotomy to remove the adult nematode. A 6-year-old female crossbreed dog presented with tachypnea, tachycardia and severe hematuria, but died shortly after presentation. Postmortem examination found the right kidney was enlarged and two adult nematodes were found in the renal pelvis. The left kidney was normal. The nematodes were collected and submitted for identifi cation. The two specimens were identifi ed as D. renale using specific identifi cation keys. Herein we present the first case of renal parasitosis by the nematode D. renale in a dog from Greece. This case highlights the need for investigation of the actual prevalence of the parasite and the use of measures for the control of its expansion aiming the protection of dogs and public health.